Alternatif Pengolahan Sampah Organik pada Bank Sampah - Sari Arlinda (CV. CENDIKIA JENIUS INDONESIA, 2025)
This community service activity aimed to provide solutions to the increasing volume of organic waste in Nanggalo District, Padang City, through the application of bioconversion technology using Black Soldier Fly larvae (maggots). The implementation method included socialization, technical training, field practice, and three weeks of mentoring involving 30 participants from three active waste banks. A participatory approach was applied to ensure effective transfer of knowledge and skills. The results showed a 35% increase in participants’ knowledge, significant improvement in maggot cultivation skills, and a 74% reduction in organic waste volume with an average maggot biomass production of 320 grams per unit per day. In addition to reducing waste generation, the activity encouraged the establishment of a new group, “Magot Hijau Nanggalo,” as a sustainability initiative. It can be concluded that community-based bioconversion technology is effective in enhancing community capacity, strengthening the role of waste banks, and contributing to the development of a circular economy at the local level.